# Equations » Logarithmic equations

`ln`(x) = e`log`(x) with  e = 2.71828182846...

Check logarithm rules if needed too.

Example 1

 3`log`(x – 2) = 1 + 4 · 3`log`(2) 3`log`(x – 2) = 3`log`(3) + 3`log`(24) 3`log`(x – 2) = 3`log`(3) + 3`log`(16) 3`log`(x – 2) = 3`log`(3 · 16) 3`log`(x – 2) = 3`log`(48) x – 2 = 48 x = 50

Example 2

 1 + 2 · 2`log`(x) = 2`log`(5x + 3) 2`log`(2) + 2`log`(x2) = 2`log`(5x + 3) 2`log`(2x2) = 2`log`(5x + 3) 2x2 = 5x + 3 2x2 – 5x – 3 = 0 D = (–5)2 – 4 · 2 · –3 = 49
 x = –(–5) + 2 · 2 or x = –(–5) – 2 · 2 x = 3 or x = –12

Example 3

 0.5`log`(x + 6) + 2 · 2`log`(x) = 0 –2`log`(x + 6) + 2`log`(x2) = 0 –2`log`(x + 6) = –2`log`(x2) x + 6 = x2 –x2 + x + 6 = 0 x2 – x – 6 = 0 (x + 2)(x – 3) = 0 x = –2 or x = 3

As x = –2 is not a solution to the original equation, the correct solution is only x = 3.

Example 4
(3`log`(x) )2 – 3`log`(x) = 0
Substitute: p = 3`log`(x)

 p2 – p = 0 p(p – 1) = 0 p = 0 or p = 1 3`log`(x) = 0 or 3`log`(x) = 1 x = 1 or x = 3

Example 5

 4`log`(x) = 2`log`(x – 2) 2`log`(x)2`log`(4) = 2`log`(x – 2) 2`log`(x)2 = 2`log`(x – 2) 2`log`(x) = 2 · 2`log`(x – 2) 2`log`(x) = 2`log`( (x – 2)2 ) x = (x – 2)2 x = (x – 2)(x – 2) x = x2 – 4x + 4 0 = x2 – 5x + 4 0 = (x – 1)(x – 4) x = 1 or x = 4

As x = 1 is not a solution to the original equation, the correct solution is only x = 4.